Performance Analysis of WBAN MAC Protocol under Different Access Periods. (28th October 2015) - Khan, Pervez; Ullah, Niamat; Alam, Md. Nasre; Kwak, Kyung Sup
The IEEE 802.15.6 is a new standard on wireless body area network (WBAN) for short-range, extremely low power wireless communication with high data rates in the vicinity of, or inside, a human body. The standard defines two contention-based channel access schemes: slotted ALOHA and carrier sense multiple access with collision avoidance (CSMA/CA) using an alternative binary exponential backoff procedure. The standard supports quality of service (QoS) differentiation through user priorities and access phases. In this study, we develop an analytical model for the estimation of performance metrics such as energy consumption, normalized throughput, and mean frame service time, employing a Markov chain model under nonsaturated heterogeneous traffic scenarios including different access phases specified in the standard for different user priorities and access methods. We conclude that the deployment of exclusive access phase (EAP) is not necessary in a typical WBAN using CSMA/CA because it degrades the overall system throughput, consumes more energy per packet, and results in higher delay for nonemergency nodes.